HOMO-LUMO, IRFRARED FREQUENCIES AND MOLECULARGEOMETRY COMPARSION STUDY OF THE STRENGTH OF BORONTRIHALIDES ACIDITY USING AM1 MOLECULAR MODELING - humadi, Salah (Iraqi Journal of Science, 2024)
AM1 Molecular Modeling has been used in the comparison of Lewis acid strength ofBoron Trihalide using available opportunities in this method such as HOMO-LUMOgap , infrared frequencies and molecular geometry. HOMO-LUMO separation wasemployed to evaluate acid strength of BX3, and results show that BI3 is more acidic thanothers and acidity has decreased up to halogen group. When complex formation betweenBX3 and dimethylamine was made , N—H bond stretching alters to red shift ( lowerfrequency) .It was found that I3BNH(CH3)2 has the lowest frequency for this bond.Geometry for these complexes , B—N bond length and degree of X-B-X angle of allmentioned complexes were also studied and pyramidal structure for complexed BX3were observed.